Evaluation and Development of Annual Drug Provides Planning at the Riau Islands Province Pharmaceutical Installation - Indri Ayu Ningsih; Dedy Almasdy; Alexie Herryandie Bronto Adi (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2019)
The high value of expired drugs in the Pharmaceutical Installation of the Riau Islands Province is one of the problems that is faced in the planning process of the Provincial Buffer Stock drug provides. The study was conducted with a qualitative approach and evaluation to understand and find the answers to the problems. The results from identification of problems that were carried out through Focus Group Discussion (FGD) are the data, human resources, and supporting factors that have a significant influence in preparing the plans for drug provides. The four main scales of priority of improvement strategies that were obtained in the preparation of drug planning are (1) Technical guidance and monitoring of evaluation of human resources at the health service center are carried out periodically by the Provincial Pharmacy Installation; (2) Availability of guidelines about the types of drugs that can be provided; (3) Provision of Standard Operational Procedure (SOP) and guidelines for the preparation of written drug providers; (4) The Pharmacy Installation Managers must be pharmaceutical professionals and not be burdened with other work. In an effort to improve data validation in the preparation of the drug provides the plan in the Pharmaceutical Installation of Riau Islands Province, the SILO application (Drug Logistics Information System) is recommended.